Urgensi Batik Mark dalam Menjawab Permasalahan Batik Indonesia (Studi Kasus di Sentra Batik Tanjung Bumi) - indah purnama sari; siswi wulandari; siska maya (Sosio e-Kons, 2019)
The purpose of this study was to examine the urgency of batik mark in answering the problems of Indonesian batik. The research uses a qualitative approach with exploratory methods. Subjects in this study were entrepreneurs or batik artisans at the Tanjung Bumi, Bangkalan, Madura batik industry center. The results showed that several problems faced by Indonesian batik were: the plagiarism of motives, the emergence of printing batik, the swift import of batik into Indonesia, the low interest of the younger generation to preserve batik art, the slow development of the batik industry due to capital and marketing problems, lack of consumer knowledge about various types of batik, the low interest of batik artisans and entrepreneurs to take care of intellectual property rights for their work, and so on. The batik mark certification program assists the government in dealing with some of the Indonesian batik problems. Batik marks can protect, preserve, develop, and promote Indonesian batik throughout the world. In its implementation, batik mark is still experiencing problems, especially the lack of interest of batik UKM to file of batik mark to the Indonesian Center for Batik Crafts, for this reason the government needs to intensify the socialization program of the urgency of batik mark to batik producers.